R. Turcan, Mihtra et le mithriacisme, París, Les Belles Lettres, 1993, 191 pp. ISBN 2-251-38023-X (Minerva. Revista de Filología Clásica, 2019)
Reseña de R. Turcan, Mihtra et le mithriacisme, París, Les Belles Lettres, 1993, 191 pp. ISBN 2-251-38023-X